Determination of the lipid composition of the GPI anchor - Aguilera-Romero, Auxiliadora; Sabido-Bozo, Susana; Lopez, Sergio; Cortes-Gomez, Alejandro; Rodriguez-Gallardo, Sofia; Perez-Linero, Ana Maria; Riezman, Isabelle; Riezman, Howard; Muñiz, Manuel (PloS one, 2021)
In eukaryotic cells, a subset of cell surface proteins is attached by the glycolipid glycosylphosphatidylinositol (GPI) to the external leaflet of the plasma membrane where they play important roles as enzymes, receptors, or adhesion molecules. Here we present a protocol for purification and mass spectrometry analysis of the lipid moiety of individual GPI-anchored proteins (GPI-APs) in yeast. The method involves the expression of a specific GPI-AP tagged with GFP, solubilization, immunoprecipitation, separation by electrophoresis, blotting onto PVDF, release and extraction of the GPI-lipid moiety and analysis by mass spectrometry. By using this protocol, we could determine the precise GPI-lipid structure of the GPI-AP Gas1-GFP in a modified yeast strain. This protocol can be used to identify the lipid composition of the GPI anchor of distinct GPI-APs from yeast to mammals and can be adapted to determine other types of protein lipidation.